Implementation of Individual Counseling of Cognitive Restructuring Techniques to Reduce Verbal Bullying of Junior High School Students in the Pesanggaran Area - Mukaromah, Lailatul; Ulwiyah, Imaratul; Mawaddati, Ika Romika (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
The general objective of this study is to determine the real changes in individual counseling with cognitive restructuring techniques in reducing verbal bullying behavior in students. The problem of this study is the frequent occurrence of verbal bullying behavior in the environment of class VII students of SMP IT Grafika Pesanggaran. The specific objective of this study is to be able to help class VII students of SMP IT Grafika Pesanggaran in reducing verbal bullying behavior that is currently occurring. Verbal bullying behavior is an aggressive statement or action in verbal form that is done intentionally and repeatedly with the aim of hurting, terrorizing, controlling, or just for fun, many triggers for verbal bullying include thoughts, feelings, and bullying behavior, verbal bullying has many negative impacts ranging from loss of self-confidence, stress, to prolonged trauma. This study uses a single-case quantitative research type with an A-B pattern consisting of two stages, namely the baseline stage and the intervention stage. The output of this study will be in the form of a scientific article that can be published in national or international journals which can later be recommended for Guidance and Counseling Teacher in reducing verbal bulliying behavior in student using cognitif restructuring techniques